(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Texture is an integral component of a text as without it, a text will be made up of isolated sentences with no connection to one another. It is achieved in a text through the use of cohesive ties that link and unify the different parts of the text. This study is a textural analysis of the #EndBadGovernanceProtest speech of President Bola Ahmed Tinubu. Its aim was to account for texture in the speech by identifying the various choices of cohesive links made by the speaker, explain the functional purposes these choices were meant to serve and how they contributed to unifying the speech in order to achieve its rhetorical purpose. The qualitative research design was adopted for this study and Halliday and Hassan’s model of Cohesion and Coherence was used as the theoretical framework. It was found that the speaker made abundant use of grammatical cohesive links especially references and conjunctions. Ellipsis and substitutions were sparsely used. Lexical cohesive links including reiteration and collocation were also used. These were identified in the text and their functional purposes elucidated. The researchers concluded that the speech was well crafted to achieve cohesion, coherence and texture in a bid to appeal to the emotions of the protesters and bring the protest to an end.